The fewer insider poachers, the more normative compliance: clues for managing poaching in the shellfish sector - Ballesteros, Hugo M. (Deviant behavior, 2021)
Shellfish poaching is an act of noncompliance with the laws that regulate fisheries governance. In this paper we explored if compliance with shellfishing laws among Galician licensed shellfish-gatherers (NW Spain) is voluntary or motivated by coercive factors. The results reveal that in those communities with a greater degree of compliance, licensed shellfish-gatherers do not poach and comply with the rules voluntarily. The conditions in these communities favor the co-management of resources in such a way that the participation of gatherers in the governance processes, internal cooperation, self-government capacity or participation in enforcement are significantly greater than in communities where there is no compliance. Furthermore, we have explored the perception of the shellfish-gatherers to minimize poaching in their communities. The interviewees distinguished two types of poachers, depending on whether they belong to the shellfishing industry or not. We made recommendations regarding policy to reduce poaching, which combine coercive and normative strategies.